2012
DOI: 10.4236/health.2012.410134
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and the associations with individual, psychosocial, and structural determinants in Swedish adolescents

Abstract: Depressive symptoms in adolescents are an increasing public health issue in Sweden and in most Western countries. Aim: To explore how individual, psychosocial, and structural determinants are associated with depressive symptoms in Swedish adolescents. Methods: A webbased questionnaire was answered by 1193 13-to 16-year-old boys (n = 566) and girls (n = 627). Stepwise logistic regressions were employed to analyse the association between depressive symptoms and various determinants at the individual level (self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 28 publications
1
18
2
9
Order By: Relevance
“…[24]. Inspired by the Ottawa Charters [25] definition of health, the PHS scale was designed based on the Salutogenic theory to identify resources that can be used to strengthen an individual and improve health. The PHS measures mental and cognitive aspects of health using positive worded questions [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24]. Inspired by the Ottawa Charters [25] definition of health, the PHS scale was designed based on the Salutogenic theory to identify resources that can be used to strengthen an individual and improve health. The PHS measures mental and cognitive aspects of health using positive worded questions [24].…”
Section: Methodsmentioning
confidence: 99%
“…The answer alternatives: “always” and “often” were categorised as having high personal affluence, while the response alternatives: “sometimes”, “rarely” and “never” had low personal relative affluence. It is important to note that absolute SES of a student is not determined by this variable; however, it is shown to be a stable indicator of relative economic affluence, which has been correlated in another study to mental health [25]. …”
Section: Methodsmentioning
confidence: 99%
“…schools are of high importance because they have an impact on students´academic, social, emotional and mental health development (Kidger et al 2012;Låftman and Östberg 2006). Several studies indicated that poor peer integration and poor teacherstudent relationships were associated with high levels of depressive symptoms in students (Gooren et al 2011;Raufelder 2014;Zetterström Dahlqvist, Landstedt, and Gillander Gådin 2012;Zimmer-Gembeck, Hunter, and Pronk 2007). Longitudinal research has identified problems in peer integration and a low quality of teacher-student relationship as predictors of depression (Landstedt, Hammarström, and Winefield 2015;Rudasill et al 2014;van Lier and Koot 2010).…”
mentioning
confidence: 99%
“…No significant correlation between education and depressive symptoms in girls in adjusted models, only in crude model. Dahlqvist et al 2012. Depressive symptoms and the associations with individual, psychosocial, and structural determinants in Swedish adolescents.…”
Section: Analysis: Narrative Synthesismentioning
confidence: 99%
“…Sweden. Design: Cross sectional, sample size 628; SES: Family Affluence Scale (FAS), "Money as friends"; Outcome: Depressive symptoms, Center for Epidemiologic Studies Depression Scale (CES-D) (34).…”
Section: Analysis: Narrative Synthesismentioning
confidence: 99%